Using Carbon Nanotubes to Absorb Low-Concentration Hydrogen Sulfide in Fluid - Wu, X.C.; Zhang, W.J.; Wu, D.Q.; Sammynaiken, R.; Wang, R.; Yang, Q. (IEEE transactions on nanobioscience, 2006)
Hydrogen sulfide is a colorless and flammable gas under room temperature. Usually hydrogen sulfide is considered to be toxic; however, the recent research revealed that hydrogen sulfide in the cardiovascular system plays the role of a vascular dilator. The physiological role of hydrogen sulfide depends on its in vivo level. As such, the measurement of hydrogen sulfide with nano-quantity resolution becomes an important subject. Existing methods generally require bulky samples and are invasive and offline. It will be significantly helpful to measure hydrogen sulfide with a small amount of tissue in a noninvasive method The first attempt was to take a blood or serum sample with a trace amount to examine the interaction between hydrogen sulfide and carbon nanotube. The carbon nanotube is chosen because of a known fact that hydrogen sulfide can be adsorbed by activated carbon. The carbon nanotube is an excellent activated carbon in this regard. Fluorescence intensity of the carbon nanotube with and without immersion of it in a hydrogen sulfide medium was examined in the study. It was found that the intensities increase as the concentrations of hydrogen sulfide increase. Furthermore, the concentration of 10 muM hydrogen sulfide in water was successfully measured